POLA ASUH AKADEMIK, KETERSEDIAAN STIMULASI, DAN PRESTASI AKADEMIK PADA REMAJA DENGAN PERBEDAAN LATAR BELAKANG PENDIIDKAN PRASEKOLAH - Srinovita, Yulya; Hastuti, Dwi; Muflikhati, Istiqlaliyah (Jurnal Ilmu Keluarga dan Konsumen, 2012)
This study aimed to analyze the differences in parenting patterns, the availability of stimulation, and academic achievement of adolescents different of preschool education background. This study also aimed to analyze the relationship between the variables. The study design was cross sectional; conducted in Sukasari and Situ Udik Village, Bogor. There were 87 adolescent who were involved in this study that selected purposively from the previous research (Hastuti, 2006). Data were collected through interviews by questionnaire. The data were analyzed with descriptive test, ANOVA different test, and Pearson correlation test. The results showed that the majority of adolescents with different preschool background had academic caring practices in the high category, avaibility of stimulation in moderate category, and academic achievement was good enough. Availability of facility to learn significantly different between groups. Availability of stimulation also significantly associated with family characteristics (family size, mother’s education, and family’s income) and academic achievement.